Efficacy and Prognostic Factors of Trans-Arterial Chemoembolization Combined With Stereotactic Body Radiation Therapy for BCLC Stage B Hepatocellular Carcinoma - Jiang, Changchen; Jing, Shenghua; Zhou, Han; Li, Aomei; Qiu, Xiangnan; Zhu, Xixu; Shen, Zetian (Frontiers in Oncology, 2021)
Purpose: This study aimed to evaluate the efficacy and safety of trans-arterial chemoembolization (TACE) followed by stereotactic body radiation therapy (SBRT) in treating Barcelona Clinic Liver Cancer (BCLC) stage B hepatocellular carcinoma (HCC) not amenable to resection and radiofrequency ablation (RFA). Methods: From February 2012 to January 2017, a total of 57 BCLC stage B HCC patients who were unsuitable candidates for resection and RFA treated with TACE combined with CyberKnife SBRT were included in this retrospective study. Patients underwent TACE for a median of two times (1–5 times) before SBRT. SBRT prescription doses ranged from 30 Gy to 50 Gy in 3–5 fractions. Results: The median follow-up time was 42 months. The objective response rate (CR + PR) was 85.9%, and the disease control rate (CR + PR + SD) was 96.5%. The local control (LC) rates were 91.1% and 84.3% at 1 and 2 years, respectively. The 1-, 2-, 3-year overall survival (OS) and the median survival time were 73.2%, 51.4%, 32.4% and 26.6 months, respectively. The 1-, 2-, and 3-year progression-free survival (PFS) were 34.2%, 21.6%, and 9%, respectively, with a median PFS time of 9.7 months. A subgroup analysis was conducted in 32 patients with AFP ≥ 200 ng/ml before TACE. OS was significantly prolonged in those with AFP that decreased by more than 75% than those with AFP that decreased by less than 75% (P = 0.018) after SBRT. The treatment was well tolerated with only one patient (1.8%) developed grade 3 gastrointestinal toxicity, and another patient developed non-classical RILD. In multivariate analysis, tumor length ≥ 10 cm and AFP ≥ 200 ng/ml were independent poor prognostic factors for OS. Conclusion: The combination of TACE and Cyberknife SBRT showed optimal efficacy with acceptable toxicity for BCLC stage B HCC.